Investigation of the prevalence and characterisation of infection by Kudoa thyrsites and K. paniformis in South African marine fish species - Henning, Sune St.Clair (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2019.